Investigation of a novel liquid desiccant wheel cooling system - Mohd Sabri, Mohd Anas (2020)
The energy consumption in cooling and forced ventilation, especially in a hot and humid climate, is widely significant and concerning. Nevertheless, the growing demand for air conditioning even in temperate climates is causing a substantial increase in energy usage and resulting in a rise in greenhouse gasses emission. It has driven the exploration of new air conditioning technologies, such as a hybrid desiccant cooling system, to save energy and reduce greenhouse gasses emission. One of the methods of a hybrid desiccant cooling system is to utilize the advantages of a wheel mechanism with liquid desiccant into one integrated system. This prototype has been developed to employ more efficient dehumidification as well as better cooling capabilities. The in-house experiment and computational simulation were used to evaluate the performance of this prototype. Based on the analysis, the coefficient of performance (COP) of this system is higher than the conventional system, and the potential can be explored for more improvement. Based on the results, the COP of the system obtained is 7.547. Then in terms of economic and environmental analysis, the system also shows a tremendous impact. In economic analysis, it shows that it only required 2.72 years to earn its investment payback. In environmental analysis, the Eco-indicator 95 tools have been used, and it shows around 0.269 points which relatively low and would have minimal impact on the environment. Even though the capital and maintenance cost of the novel liquid desiccant wheel cooling system is much higher than the conventional HVAC system, but its running cost is relatively lower. Thus, the novel wheel liquid desiccant cooling system is cost-effective and environmentally friendly.